Splitting the Marital Home: Gendered Property Division and Postdivorce Foreclosure. Issue 5 (4th July 2019) - Lichtenstein, Bronwen; Johnson, Ida M.
ABSTRACT: Divorce proceedings often involve splitting the marital home and contested claims over property and other assets. This case study examines the divorce–foreclosure nexus through key informant interviews, analysis of divorce files and foreclosure notices, and a review of court records on debt, remarriage, and criminal offending. We found that property disposition is a gendered process, with men receiving the marital home 1.7 times more often than women, even though they had more court debt, job instability, and criminal offending than their wives. Male defendants who hired an attorney received the house 85% of the time (52% for women defendants with an attorney). In postdivorce, men were more likely than women to remarry, have second mortgages, and to reoffend. We conclude that "equal" rather than "equitable" property division would reduce women's structural disadvantage in divorce settlements and postdivorce home ownership.